PERANCANGAN DAN PENGUKURAN KEY PERFORMANCE INDICATORS (KPIs) DENGAN KONSEP GREEN SUPPLY CHAIN MANAGEMENT STUDI KASUS: FULFILLMENT WAREHOUSE - Tjoe, Jerry Chandra; Kosasih, Wilson; Tjhia, Andres (Universitas Tarumanagara, 2024)
This research was conducted at a Fulfillment Center company, which is engaged in 3PL (Third Party Logistics). The design and performance measurement this time uses a Green Supply Chain Management approach and is adjusted to the company's vision and mission, resulting in 40 KPIs that have been successfully designed. After that, the company only validated 24 KPIs, then modeled Green Supply Chain Operation References with 4 perspectives, namely plan, source, delivery, and return. 4. From the assessment results of the Objective Matrix (OMAX) method and Traffic Light System, 18 performance indicators are green, 5 performance indicators are yellow, and 1 performance indicator is red. In addition, each perspective also has a score, among others: the source perspective with an achievement score of 9.719, followed by the plan perspective with a score of 9.536, then the delivery perspective with a score of 7.753, and the worst perspective is the return perspective with a score of 6.509.